2017
DOI: 10.1038/ng.3816
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-genome sequencing identifies rare genotypes in COMP and CHADL associated with high risk of hip osteoarthritis

Abstract: We performed a genome-wide association study of total hip replacements, based on variants identified through whole-genome sequencing, which included 4,657 Icelandic patients and 207,514 population controls. We discovered two rare signals that strongly associate with osteoarthritis total hip replacement: a missense variant, c.1141G>C (p.Asp369His), in the COMP gene (allelic frequency = 0.026%, P = 4.0 × 10, odds ratio (OR) = 16.7) and a frameshift mutation, rs532464664 (p.Val330Glyfs*106), in the CHADL gene tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 42 publications
0
67
1
1
Order By: Relevance
“…CHADL, encoding Chondroadherin-Like Protein, is involved in collagen binding and is a negative modulator of chondrocyte differentiation. The OA susceptibility allele rs117018441-T, located in an intron of CHADL, marks higher expression of CHADL compared to rs117018441-G in skeletal muscle and adipose tissue (GTEx) [5,35]. This may indicate that increased expression of CHADL has a negative regulatory role both in bone and cartilage and that a therapeutic strategy could be the inhibition of this gene.…”
Section: Differential Expression Analysis Of the Gene Expression Levementioning
confidence: 99%
“…CHADL, encoding Chondroadherin-Like Protein, is involved in collagen binding and is a negative modulator of chondrocyte differentiation. The OA susceptibility allele rs117018441-T, located in an intron of CHADL, marks higher expression of CHADL compared to rs117018441-G in skeletal muscle and adipose tissue (GTEx) [5,35]. This may indicate that increased expression of CHADL has a negative regulatory role both in bone and cartilage and that a therapeutic strategy could be the inhibition of this gene.…”
Section: Differential Expression Analysis Of the Gene Expression Levementioning
confidence: 99%
“…This year, five large genome-wide association study (GWAS) added to our knowledge regarding OA genetic risk. These included one hand OA study 1 , one hip OA study 2 , and two knee OA studies in Chinese cohorts 3,4 . One additional study examined variation associated with neuropathic pain following total joint replacement 5 (summarized in Table II).…”
Section: Geneticsmentioning
confidence: 99%
“…With the rapid development of genetic epidemiology and genetic assay technologies, gene polymorphisms are found to play a crucial role in the initiation and progression of OA and have received more and more attentions over recent years . So far, genome‐wide association studies have demonstrated that single nucleotide polymorphisms (SNPs) in a range of genes, such as growth differentiation factor 5 gene, Frizzled‐related protein gene, cartilage oligomeric matrix protein gene and chondroadherin‐like gene, and fat mass and obesity‐associated gene, are associated with susceptibility to OA. Apart from that, increasing literature elucidated a vital role of inflammation during the pathogenesis of OA, and various inflammatory cytokine genes which conferred susceptibility to OA are still being investigated .…”
Section: Introductionmentioning
confidence: 99%